Influência da temperatura e do patamar de sinterização na produção de agregados sintético produzidos a partir do resíduo do processo bayer com adição de biomassa - MARINHO, Rodrigo Nascimento (2022)
Mining is an important activity for obtaining raw materials for industry as well as for the economy of a country, however, tons of solid waste are generated every year, usually without an appropriate destination. As is the case of the residue generated from bauxite beneficiation called red mud, which generates about 1 to 2 tons of this residue for every ton of bauxite beneficiated, the fact is that the amount remaining of this residue is very large while a very small percentage of it is reutilized. Urban residues also cause various problems for the environment, like the residue from the processing of the açaí pulp, more specifically the stone fuit, which is unappropriately discarded in urban centers. Nowadays the preoccupation with the preservation of the environment is eminent, leveraging researches with the objective of reusing the most diverse residues of the industry. The residue in question (red mud) can be used to generate a material with interesting mechanical characteristics to be used in civil construction. Research indicates using it in structural concrete is an economically viable alternative, considering the volume of natural aggregate used daily in civil construction is very large. While having an adequate destination for this waste, it also reduces the exploitation of natural resources such as gravel and rolled pebble, which, due to their excessive exploration, cause environmental liabilities. The objective of this work was to synthesize synthetic aggregates from those two residues, in conjunction with the use of clay and sand. The percentages of raw materials were fixed at 60, 20, 15 and 5 % of red mud, silica, coal made from the stone of the açaí and clay respectively, intending to analyze the effects of temperature and burning level on the solid state reactions in the aggregate. The raw materials were submitted to a beneficiation process: drying, brittling and screening on 100 mesh Tyler, subsequently a percentage of 15% to 20% of water was added for the extrusion process, and then burning was done at the temperature of 1100 and 1200 ºC with sintering levels of 3 and 4.5 hours. The aggregates were then characterized to determine their physical and morphological properties. The aggregates sintered at 1100 ºC presented apparent specific mass of 2.13 g/cm3 at 3h and 1.87 g/cm3 at 4.5h, while the aggregates sintered at 1200 ºC presented results of 2.01 g/cm3 at 3h and 2.19 g/cm3 at 4.5h. In the scanning electron microscopy it was possible to identify the presence of the secondary mullite phase presenting a structure that resembles needles in all materials, where the presence of this phase is fundamental importance to confer a good mechanical resistance to the material. In conclusion, the use of red mud in the production of synthetic aggregates is an important alternative for the use of this waste that has been accumulated for decades, as well as bringing economic benefits to the industry and especially to the environment.